P42. Is my heart beating for you? Bodily reactions during reading of emotion words differentiate good from bad and self from other – Implications for clinical research. Issue 8 (August 2015) - Weis, P.; Herbert, C.
<x xml:space="preserve">Abstract</x> Research background Social, cognitive and affective neuroscience suggests that emotion and language are closely related (e.g. Gendron et al., 2012). Disconnectivity of emotions from language and vice versa is central to many clinical disorders. Here, a multimodal paradigm to investigate emotional processing in the brain and the body is presented (Herbert et al., 2011a, b, 2012). The paradigm uses words that are related to own or other people's emotions. In the present study, we measured bodily responses to these words while subjects intuitively judged them for emotional valence. Method Word phrases consisting of a pronoun and a noun were presented on a computer screen. Nouns varied in valence (positive/neutral/negative), pronouns in self-reference (self/other/no reference), resulting in a 3 ∗ 3 design. The subject's task was to judge the emotional valence of the words. Reaction times, skin conductance (EDA), facial expressions (fEMG) and heart rate (HR) were recorded. Results Pronoun–noun-phrases with positive or negative nouns were evaluated faster than pronoun–noun-phrases with neutral nouns. Self-related positive pronoun–noun phrases (e.g. my happiness) were judged and responded to the quickest. This special processing of positive stimuli when related to the self is in line with previous EEG-studies reporting preferential processing of self-referenced positive stimuli in healthy subjects (e.g. Herbert et al., 2011). Physiologically, emotional pronoun-noun pairs elicited an increase in phasic heart rate compared to pronoun–noun pairs of neutral meaning. The same pattern seemed to emerge for electrodermal activity while fEMG varied as a function of both, stimulus valence and self-reference. Conclusion In healthy subjects, there exists a self-positivity bias facilitating responses to self-related positive stimuli. This bias is going to be reversed in participants with elevated depression scores and appears to be modulated further by personality dimensions such as narcissism. Thus, spontaneous valence judgments suffice to alter bodily responses to emotion words in healthy subjects as a function of the word's personal reference and its emotional content supporting the embodied nature of emotions in language. The next step will be to investigate clinical samples with this paradigm to determine the relevance of bodily processing in the comprehension of emotions in various clinical populations suffering from affective (e.g. depression) or psychotic disorders (e.g. schizophrenia).